Anthropometry, body fat and central adiposity in LBW and NBW Indian children aged 3.5 to 4 years - Aneesh, Mitravinda; Ghugre, Padmini S. (Early human development, 2019)
India has a high prevalence of low birth weight. Evidence indicates that poor fetal growth and rapid postnatal weight gain are associated with adiposity. (i) To study the differences between the anthropometry, body fat measures of LBW and NBW children and (ii) To find out if there is any relationship between birth weight, change in weight SD and body fat measures of these children. Cross-sectional study. We studied 396 children aged between 3.5 and 4 years who were beneficiaries of government-run anganwadis in urban slums of Mumbai city, India. Birth weight, current weight, height, skinfold thicknesses and waist circumference. Change in weight SD and body fat (%) were calculated. WHOAnthro was used to compute the z scores. Parent's education, income and breastfeeding history was recorded. The mean change in weight SD of LBW and NBW groups were 1.01 ± 1.4 and −0.73 ± 1.13 respectively (p < 0.001). LBW children were lighter and shorter than NBW ones but had similar body fat (%) and central adiposity measures. In LBW and NBW children, birth weight Z score and change in weight SD were positively related to body fat (%) and waist circumference. Children in this study belonged to low socioeconomic section. Despite this, LBW displayed a tendency towards accumulating body fat particularly, abdominal fat for lower body weight. Birth weight and postnatal weight change predict body fat and waist circumference in LBW and NBW children. •During the early postnatal years, LBW children are likely to experience catch-up growth.•Most of these children are likely to demonstrate catch-up fat phenomenon.•Both, birth weight and change in weight SD are predictors of total body fat (%) and central body fat.•Growth monitoring should be used to identify children at-risk childhood obesity.